Knowledge and Use of Public Relations Artificial Intelligence Tools Among Practitioners in Awka - Chinonso Chinaemerem Adikuru; Dennis O. Abutu (Darul Yasin Al Sys, 2025)
This study explores the knowledge and application of Artificial Intelligence (AI) tools among Public Relations (PR) practitioners in Awka, Nigeria. Adopting a qualitative research design, data were gathered through in-depth interviews with ten purposively selected PR professionals based in the city. The findings indicate that while there is a general awareness of AI tools among practitioners, this awareness is predominantly limited to general-purpose applications such as ChatGPT, Grammarly, and Quillbot. There is a marked deficiency in both knowledge and utilization of industry-specific AI tools such as Meltwater, Cision, and Sprinklr—platforms designed to support media monitoring, sentiment analysis, strategic communication, and automated content generation. Actual usage of AI tools in PR practice remains minimal and largely confined to surface-level tasks such as text editing and paraphrasing. The study concludes that there is a significant skills and awareness gap that may hinder effective AI integration into PR workflows. Accordingly, it recommends targeted capacity-building initiatives, including workshops, certification programmes, and collaborative training involving technology providers and academic institutions. Additionally, the study underscores the importance of hands-on exposure through mentorship schemes and tool demonstrations. Finally, it calls for the development of ethical guidelines to ensure responsible AI adoption, with particular attention to transparency, accountability, and data privacy in professional communication contexts.